Sensory and chemical effects of two alternatives of prefermentative cold soak in Malbec wines during winemaking and bottle ageing - Casassa, Luis Federico; Sari, Santiago Eduardo (2018)
Two alternatives of cold soak (CS), traditional external refrigeration (CS‐T) and use of solid CO2 (CS‐DI), were evaluated in Malbec wines and contrasted against a control (C) during winemaking and up to 24 months of bottle ageing. Sugar consumption up to 5 g L day‐1 was observed in CS‐T during the CS period. Both the viability of the population of Saccharomyces and non‐Saccharomyces were maintained during CS. CS‐T was detrimental for the anthocyanin and phenolic content and caused a reduction of absorbance in the visible spectrum of the wines relative to C and CS‐DI. CS‐DI had an early positive effect in the anthocyanin content and chromatic properties, but this effect subsided after 6 months of bottle ageing relative to C. From a sensory standpoint, CS‐T had the lowest colour saturation and a marked acetaldehyde character. CS‐DI wines were the most saturated in colour at press and early ageing, whereas a balsamic‐like aroma developed during bottle ageing. C wines were characterised by red fruits aroma, reduction and astringency early during winemaking, but a decrease in astringency and the reduction character occurred during bottle ageing.